First discoveries of colonies of the rare ant species Camponotus tergestinus Müller, 1921 (Hymenoptera: Formicidae) in situ - Gregor Bračko (Natura Sloveniae)
The rare ant species Camponotus tergestinus Müller, 1921 has so far been reported from few central and southern European localities, but none of its colonies have ever been recorded in situ. In 2016 and 2017, two colonies were found at Lipica (SW Slovenia), the first nesting on Quercus pubescens at the height of 3.2 m, the second on Q. cerris at the height of 2.2 m. Both nests had two entrances each. Numerous visits have been carried out at the site in order to observe both colonies. Based on available data, Camponotus tergestinus is an arboricolous species having a strong association with oaks. Its arboricolous and presumably nocturnal habits could be the main reasons for the paucity of available data. A list of all known localities, retrieved from both published and unpublished records, is also provided.